Dakwah Pasca Covid 19 - Ahmad Taufik (STAI Bumi Silampari, 2020)
In preaching, there are important things which are also factors of success or failure of preaching, namely motivation. Motivation is important and the subject of everything. In motivation, it contains three main components, namely moving, directing and supporting human behavior. In other words, motivation directs individual behavior towards a goal to maintain and support the behavior, while the environment must strengthen the intensity and direction of individual encouragement.